Time Series Analysis of Sales Quantity In An Automotive Company and Estimation By Artificial Neural Networks - Vildan Öz; Seher Arslankaya (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The automotive sector is an indicator sector that sheds light on theeconomies of the countries. Demand forecasting in such an important sector, asit is in every sector, is an important work topic. Two important problems of areal production environment are uncertain demand and unbalanced productiontimes. These two parameters affect the semi-finished and finished productinventory levels which lead to an increase in the total cost of the productionsystem. Demand forecasting is the estimation of how much consumers and servicesthey will demand in the future with the aid of variables. In this study,automotive sector, one of the most important sectors of today, has beenestimated demand of sales quantities. Estimation results with RegressionAnalysis (RA) and time series are compared with the estimation results made withartificial neural networks.